Development of Purple Sweet Potato-Based Ice Cream Product - Umnat, Suparat; Penjumras, Patpen; Pokkaew, Rattaphong; Saiphong, Wilasinee; Tongsukngam, Nanthikan; Wattananapakasem, Isara (Journal of Technical Education Science, 2023)
The popularity of ice cream is increasing in tropical countries such as in Thailand. Purple sweet has high anthocyanin content which provides an attractive purple appearance for ice cream consumption. The purposes of this study were to determine the effects of the ratio of purple sweet potato mash and water, and concentration of carboxymethyl cellulose (CMC) as a stabilizer on the properties of ice cream. The different ratios of purple sweet potato mash and water at 40:60, 50:50, and 60:40 were investigated. The results showed that the ratios of purple sweet potato mash and water had a significant effect (p≤0.05) on physical properties. The overrun, a* and b* values, and melting rate decreased with an increase in purple sweet potato mash. There was a significant (p≤0.05) difference in sensory characteristics scores of appearance, taste, texture, and overall acceptance. The scores decreased with an increase in purple sweet potato mash. Therefore, the selected ratio was 40:60 between purple sweet potato mash and water. In another study, the concentration of CMC at 0.2, 0.3, and 0.4% of total ingredients on the properties of ice cream was observed. The results demonstrated that overrun and melting rates decreased with an increase in CMC. In addition, an increase in CMC showed significantly (p≤0.05) superior taste and texture scores. Therefore, the selected condition for product development of purple sweet potato-based ice cream was the ratio of purple sweet potato mash and water at 40:60 and 0.4%CMC.